Odpowiedź :
Odpowiedź :
[tex]5log_{\frac{1}{4} } 2+log_{4^{-1}} \sqrt[4]{16} -log_{2^{-2}} 16=log_{\frac{1}{4} } 2^5+log_{\frac{1}{4} } 2-log_{\frac{1}{4} } 2^4=log_{\frac{1}{4} } (2^5 \cdot 2)-log_{\frac{1}{4} } 2^4[/tex]
[tex]=log_{\frac{1}{4} } 2^6-log_{\frac{1}{4} } 2^4=log_{\frac{1}{4} } \frac{2^6}{2^4} =log_{\frac{1}{4} } 2^2=log_{\frac{1}{4} } 4= -1[/tex]
odp : D
Skorzystaliśmy z własności logarytmu :
[tex]m \cdot log_{a} b=log_{a} b^m[/tex]
[tex]log_{a} (b_{1} \cdot b_{2} )=log_{a}b_{1} +log_{a} b_{2}[/tex]
[tex]log_{a} \frac{b_{1} }{b_{2} } =log_{a} b_{1} -log_{a} b_{2}[/tex]
Oraz definicji logarytmu :
[tex]log_{a} b=c[/tex] ⇔ [tex]a^c=b[/tex]
[tex]5\log_\frac142+\log_{4^{-1}}\sqrt[4]{16}-\log_{2^{-2}}16=\\\\= \log_\frac142^5+\log_\frac142-\log_\frac142^4=\\\\= \log_\frac14(2^5\cdot2:2^4) =\\\\= \log_\frac142^{2}=\\\\= \log_\frac144=\\\\= \log_\frac14\left(\frac14\right)^{-1} =\\\\ = -1\log_\frac14\frac14=\\\\=-1\cdot1=\\\\=-1[/tex]
Korzystamy z działań na potęgach i logarytmach:
[tex]a^{-n}=\left(\dfrac1a\right)^n\,,\qquad\qquad a^x\cdot a^y=a^{x+y} \\\\ n\cdot\log_ab=\log_a\big b^n\\\\ \log_ax+\log_ay=\log_a(x\cdot y) \\\\ \log_ax-\log_ay=\log_a(x:y) \\\\\log_aa=1[/tex]